Graphic Library Optimization for MIPS Architecture - Novkovic, Teodora; Lukac, Zeljko; Jovanovic, Petar; Kastelan, Ivan (Elektronika ir Elektrotechnika, 2020)
The aim of this paper and research was to analyse the efficiency of the compiler-generated code for the graphics library and to present results obtained by optimization for the MIPS (Million Instructions Per Second) architecture. Libpng is the official Portable Network Graphics reference library for use in applications that read, create, and manipulate PNG (Portable Network Graphics) raster image files. Given the data structure in the PNG files, as well as the capabilities of the MIPS instruction set, it was expected that significant improvements could be made. Graphic library libpng is optimized by using MIPS instruction set extension and tested on MIPS Malta 74K platform. Test results show, that by using MIPS optimization test, execution times are substantially improved. Our libpng optimization have achieved performance increase of 10 %–78 % depending on optimized routine.